A Descriptive Study on English Speaking Skills Learning Strategies of EFL Students at Al Fatah Education Foundation - Evha Nazalatus S Sy; Yuliarsih; Fredy Yunanto; Fani Nurcahya Rhamadani; Putri Kamilia Trisna (CV. ULIL ALBAB CORP, 2024)
This study aims to identify and analyze the speaking skills learning strategies applied by teachers at the Al Fatah Education Foundation in the context of learning English as a foreign language (EFL). Using a qualitative descriptive approach, the study involved EFL students and English teachers at the foundation as research subjects. Data was collected through observations, semi-structured interviews, and questionnaires that were analyzed using thematic analysis techniques. The results showed that teachers used various learning strategies, such as role plays, group discussions, presentations, and information gap activities to improve students' speaking skills. These strategies have proven to be effective in creating an interactive learning environment and supporting the development of students' speaking skills in a more authentic context. In addition, constructive feedback from teachers and the use of learning technology also contribute to the improvement of students' speaking skills. This study provides important insights into the application of speaking learning strategies in EFL and suggests that educators should pay attention to the diversity of techniques that can increase student participation as well as their motivation in speaking English. These findings are also expected to be a reference for curriculum development and further research in the field of foreign language teaching.